2018
DOI: 10.1002/anie.201805526
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting the Synthetic Potential of Sesquiterpene Cyclases for Generating Unnatural Terpenoids

Abstract: The substrate flexibility of eight purified sesquiterpene cyclases was evaluated using six new heteroatom-modified farnesyl pyrophosphates, and the formation of six new heteroatom-modified macrocyclic and tricyclic sesquiterpenoids is described. GC-O analysis revealed that tricyclic tetrahydrofuran exhibits an ethereal, peppery, and camphor-like olfactoric scent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
51
0
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(61 citation statements)
references
References 43 publications
2
51
0
8
Order By: Relevance
“…The elongation of GPP with 8a and 8b using FPPS also resulted in the two enantiomerso f4methyl-FPP (10)w ith high enantiomeric purity,a sd emonstrated by dephosphorylation with CIP followed by GC/MSa nd enantioselective GC analysis (Figures S10a nd S11). Ap reparative-scaler eaction with 8a and product isolation for structure elucidation by NMR (Table S2, Figures S12-S18) confirmed the structure of 4-methylfarnesol (12). Its optical rotation[ a] 20 d = À6.0 (CH 2 Cl 2 , c 0.25) allowed to assign the absolutec onfiguration of (S)-4-methylfarnesol (12 a)f or the product from 8a by comparison to literature data for the same enantiomer ([a] d = À10.7, hexane), [14] andc onsequently (R)-12 b was obtained from 8b.B ased on the same sign for the opticalr otation [a] 20 d = À5.5 (CH 2 Cl 2 , c 0.2) of 11 a formed from 8a,a nd on the same GC elution order on ac hiral stationary phase, analogous absolutec onfigurations werea ssignedf or (S)-11 a and (R)-11 b.…”
mentioning
confidence: 65%
See 1 more Smart Citation
“…The elongation of GPP with 8a and 8b using FPPS also resulted in the two enantiomerso f4methyl-FPP (10)w ith high enantiomeric purity,a sd emonstrated by dephosphorylation with CIP followed by GC/MSa nd enantioselective GC analysis (Figures S10a nd S11). Ap reparative-scaler eaction with 8a and product isolation for structure elucidation by NMR (Table S2, Figures S12-S18) confirmed the structure of 4-methylfarnesol (12). Its optical rotation[ a] 20 d = À6.0 (CH 2 Cl 2 , c 0.25) allowed to assign the absolutec onfiguration of (S)-4-methylfarnesol (12 a)f or the product from 8a by comparison to literature data for the same enantiomer ([a] d = À10.7, hexane), [14] andc onsequently (R)-12 b was obtained from 8b.B ased on the same sign for the opticalr otation [a] 20 d = À5.5 (CH 2 Cl 2 , c 0.2) of 11 a formed from 8a,a nd on the same GC elution order on ac hiral stationary phase, analogous absolutec onfigurations werea ssignedf or (S)-11 a and (R)-11 b.…”
mentioning
confidence: 65%
“…[11] In addition to such natural enzymes ystemsf or the biosynthesis of homoterpenes, several canonical TSs exhibit ar emarkable plasticity that allows the conversion of non-natural substrate analoguesw ith additional Meg roupso rh eteroatoms. [12] This strategy can give a rapid and potentially enantioselective access towards methylated or functionalised terpene analogues, but previousw ork depended on the chemical synthesis of the oligoprenyl diphosphate analogues. Here we report on the stereoselective synthesis of homologated IPP derivatives, the enzymatic incorporation into methylated GPP and FPP analogues,a nd their TScatalysed conversion into non-naturalhomoterpenes.…”
mentioning
confidence: 99%
“…It is useful to evaluate the enzymatic conversion of other substrates, like monoterpene precursors or synthetic substrates as tested by Oberhauser et al by the PTS, with different buffers to test whether the formation of different products can be detected . To complete these NMR based studies, enzymatic experiments like homology modeling of PTS and further deuteration tests on reaction mechanisms of the other main products could be essential.…”
Section: Resultsmentioning
confidence: 99%
“…GC-MS analyses of the pentane extractable products obtained from phosphorylation/cyclization reactions starting from 3 and 4 catalyzed by ScGDS, AaADS, 7epizingiberene synthase from Solanum habrochaites (ShEZS), and (À)-germacradiene-4-ol synthase from Streptomyces citricolor (ScGD4OL) showed that the respective natural products had been generated (20)(21)(22)(23) (Figure 2, S19-30). [30,32,44] Furthermore, using methylated prenol analogues 12 and 13 directly yielded the desirable unnatural semiochemicals (S)-14,15-dimethylgermacrene D (24), (S)-12-methylgermacrene D (25), and (S)-15-methylgermacrene D (26) (Figure 2). Similarly, using 4-hydroxyprenol (11) and 4 to form 15 followed by addition of AaADS yielded dihydroartemisinic aldehyde (27).…”
Section: Zuschriftenmentioning
confidence: 99%